Hubungan Antara Terpaan Iklan Aplikasi Halodoc Dan Terpaan Persuasi Reference Group Dengan Minat Untuk Menggunakan Aplikasi Halodoc Sebagai Sarana Konsultasi Dengan Dokter - Badri Ilham Ramadhan; Tandiyo Pradekso (Interaksi Online, 2021)
This research is based on the service level of using telemedicine in Indonesia, namely HaloDoc. The purpose of this study was to see whether there was an influence on exposure to HaloDoc application advertisements and the Persuasion of the Reference Group on consumer interest in using the HaloDoc application as a means of consulting with doctors. Advertising Exposure theory and Reference Group theory are used to explain the influence between variables in this study. The population in this study were men and women aged 29-49 years who had received HaloDoc application advertisements or persuasion reference groups. The sampling technique used non-probability sampling with a sample size of 60 respondents.The analysis used to check the hypothesis in this study does not have the meaning of Kendall's tau b. Data processing uses the Statistical Package for Social Science (SPSS) 16.0 Version program. Hypothesis test results between exposure to HaloDoc advertising (X1) and interest in using the HaloDoc application (Y) resulted in a significance value of 0.024 <0.05 with a coefficient value of 0.236. Meanwhile, the results of hypothesis testing between the Persuasion of the Reference Group (X2) and the interest in using the HaloDoc (Y) application resulted in a significance value of 0.000 <0.01 with a coefficient value of 0.371.The results showed that there was an influence between exposure to HaloDoc application advertisements and persuasion by the Reference Group on the interest in using the HaloDoc application as a means of consulting with doctors so that both hypotheses could be accepted. So it can be ignored that the higher the exposure to HaloDoc application Ads and the Persuasion of the Reference Group, the higher the consumer interest in using the HaloDoc application.